PEMBERDAYAAN MASYARAKAT KECAMATAN LEPAR PONGOK DALAM PENGELOLAAN SAMPAH GUNA MENYONGSONG DESTINASI WISATA PULAU LEPAR - Irwan Dinata (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2015)
The tourism sector as a service industry is one of the fields that is expected to contribute significantly to regional development.This tourism activity if managed properly can be one of the potential contributors to income in regional and national economic growth. Tourism is not only a source of foreign exchange but can also expand employment opportunities arising from the involvement of a number of other sectors in it. For the Bangka Belitung Islands Province, tourism is one of the sectors that can be relied upon to anticipate the post tin mining era which has so far been the flagship in Bangka Belitung, because in addition to its strategic location, tourism also provides multiplier effects that can encourage economic growth.To build a tourist island, it is necessary to prepare various aspects. One of them is the cleanliness of the island. Waste generated by the local community and the local environment should be managed properly. Waste generated by the local community and the local environment should be managed well, especially if the waste can provide benefits either directly or indirectly.